2017
DOI: 10.3343/alm.2017.37.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-C Genotype and Killer Immunoglobulin-like Receptor-Ligand Matching in Korean Living Donor Liver Transplantation

Abstract: BackgroundThe interaction between killer immunoglobulin-like receptors (KIRs) and HLA class I regulates natural killer (NK) cell cytotoxicity and function. The impact of NK cell alloreactivity through KIR in liver transplantation remains unelucidated. Since the frequency of HLA-C and KIR genotypes show ethnic differences, we assessed the impact of HLA-C, KIR genotype, or KIR-ligand mismatch on the allograft outcome of Korean liver allografts.MethodsOne hundred eighty-two living donor liver transplant patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…They also showed a positive relationship between AR and the number of C2 group HLA alleles. Nevertheless, KIR genotypes and the number of KIR activating/inhibiting KIRs were not related to the allograft outcome and did not have a statistically significant effect on graft survival [ 74 ]. Legaz et al reported that KIR2DL3 and KIR2DS1 in recipients correlated with the increased incidence of AR in the presence of donor C2 ligands.…”
Section: Nk Kir and Solid Organ Transplantationmentioning
confidence: 99%
“…They also showed a positive relationship between AR and the number of C2 group HLA alleles. Nevertheless, KIR genotypes and the number of KIR activating/inhibiting KIRs were not related to the allograft outcome and did not have a statistically significant effect on graft survival [ 74 ]. Legaz et al reported that KIR2DL3 and KIR2DS1 in recipients correlated with the increased incidence of AR in the presence of donor C2 ligands.…”
Section: Nk Kir and Solid Organ Transplantationmentioning
confidence: 99%
“…The studies included were published as early as 2007 by Kreijveld et al (2007) and Kunert et al (2007), while the latest was published in 2017 by Jafari et al (2017) and Littera et al (2017). Most of the studies were done in western countries (Kreijveld et al 2007;Kunert et al 2007;La Manna et al 2013;Legaz et al 2013;Littera et al 2017) and only three were conducted in Asian countries (Alam et al 2015;Jafari et al 2017;Lee et al 2017). Among the eight studies included, two delved on liver transplantation rejection (Legaz et al 2013;Lee et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were done in western countries (Kreijveld et al 2007;Kunert et al 2007;La Manna et al 2013;Legaz et al 2013;Littera et al 2017) and only three were conducted in Asian countries (Alam et al 2015;Jafari et al 2017;Lee et al 2017). Among the eight studies included, two delved on liver transplantation rejection (Legaz et al 2013;Lee et al 2017). Furthermore, La Manna et al (2013) and Littera et al (2017) focused on chronic types of rejection while the others involved acute graft rejection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations